Computer Vision, Imaging and Computer Graphics Theory and Applications: 14th International Joint Conference, VISIGRAPP 2019, Prague, Czech Republic, February 25–27, 2019, Revised Selected Papers - Cláudio, Ana Paula; Bouatouch, Kadi; Chessa, Manuela; Paljic, Alexis; Kerren, Andreas; Hurter, Christophe; Tremeau, Alain; Farinella, Giovanni Maria (Communications in computer and information science, 2020)
Computer Graphics Theory and Applications -- Human Computer Interaction Theory and Applications -- Information Visualization Theory and Applications -- Computer Vision Theory and Applications.